Teachers’ worklife, mental health, and job burnout: Cases of Thailand and Indonesia - Araya Piyakun; Herli Salim (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study aimed to: i) explore the worklife areas, mental health, and job burnout among Thai and Indonesian teachers; ii) investigate the roles of worklife areas on mental health and burnout; and iii) compare the two groups of teachers. The participants consisted of 340 teachers (210 Thai teachers and 130 Indonesian teachers) who voluntarily responded to the online questionnaire. The instruments for data collection included the depression anxiety stress scales-21, the areas of worklife survey, and the Maslach Burnout Inventory-Educators Survey. Frequency, mean, standard deviation, Pearson correlation coefficient, and multiple regression analysis were utilized to analyze the data. The results revealed that the mean scores for six areas of worklife were comparable across the two groups, whereas the mean scores for mental health and job burnout were distinct. In addition, it was discovered that teachers’ worklife could predict their mental health and job burnout in Thailand and Indonesia. However, the predictive patterns varied for each scale of mental health and burnout, as well as across the two groups. The study’s findings shed light on the impacts of workplace factors on teachers’ mental well-being.